Identifikasi Pencemaran Air Lindi pada Kawasan Asrama di Kampus Universitas Udayana dengan Menggunakan Metode Geolistrik Konfigurasi Wenner - Pratama, Maulana Rizki; Putra, I Ketut; Nurmalasari, Ni Putu Yuni; Sumadiyasa, Made; Sandi, I Nengah; Baskoro, Winardi Tjahyo (Kappa Journal, 2023)
Dormitory land in the Udayana University area is often used as a place to dispose of garbage. Basically leachate contains metal content such as zinc (Zn) and mercury (Hg) which seep into the soil. Identification to determine the presence of leachate at a certain depth, can use the Wenner Configuration Geoelectrical Method. From the data obtained then processed using Res2dinv it was found that the leachate content in the Udayana University Dormitory Area is found at a distance of 33m, 43m, 63m, 83m, from the pile of garbage and a depth of 1.25 - 3.75m below the surface of the pile of garbage for coordinates 115.165240 BT, 8.798640 LS to 115.164955 BT, 8.799100 LS and a distance of 62m, 72m, 82m, from the garbage pile and a depth of 1.25 – 6.38m below the surface of the garbage pile at coordinates 115.165091 BT, 8.798557 LS to 115.164730 BT, 8.799021 LS.